Screening of various polyethylene terephthalate chain extenders in a melt polymerization set-up - Özdemir, Ayşenur. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Polyethylene terephthalate (PET) is one of the most important and common polyester in the industry. It is produced by the reaction of ethylene glycol (EG) with terephthalic acid (TPA) or dimethyl terephthalate (DMT). The polymerization can be carried out through melt then, if high molecular weights are targeted, solid state polymerization. PET has excellent chemical resistance, high mechanical strength and high thermal stability. Therefore it is used in very different application areas. For every application area PET have different molecular weight values. As the molecular weight requirement increases the production of PET becomes difficult via melt polymerization. Solid state polymerization (SSP) is used for high molecular weight PET production. SSP’s disadvantage is that reaction time is very long and therefore expensive. Also, during processing of PET, molecular weight decreases because of the heat applied. All these problems can be addresed via chain extenders. In this study, chain extension reactions of PET with four different chain extenders, carbonyl biscaprolactam, 1,3-phenylene-bisoxazoline, DE and SO were carried out and their effect on molecular weight were investigated. Structures of DE and SO will not be noted in this thesis due to the confidentiality of the study.
Keywords: Polyethylene terephthalate.